Community Participation in Reducing Flood Disaster Risk in Boyantongo Village, South Parigi Sub-district, Parigi Moutong District - Rahmat; Novarita, Amalia; Arsy, Risma Fadhilla (Tadulako Social Science and Humaniora Journal, 2024)
Boyantongo Village is one of the villages in the South Parigi Sub-district, Parigi Moutong Regency, which has experienced flooding several times during the rainy season. Flash floods that hit Boyantongo Village occurred on August 25, 2012, causing 142 residents of Boyantongo Village to flee Flash floods in Boyantongo Village occurred again on July 11-13, 2020 flash floods occurred at 21.00 WITA causing 18 Boyantongo Village residents to flee. The purpose of this study was to determine the level of community participation in reducing the risk of flood disasters in Boyantongo Village. The study used a sample survey method, survey research is one research approach that is generally used for extensive data collection. At the same time, the data collection techniques used in this study used instruments in the form of questionnaires. The research was conducted by distributing questionnaires to 67 households. The results showed that the potential for flooding is in Hamlet I, Hamlet III, and Hamlet IV. Aspects of community understanding of basic disaster knowledge, from Hamlet I is categorized as quite good, Hamlet III is categorized as good and Hamlet is categorized as quite good. Community knowledge in disaster mitigation during floods is categorized as low. It shows that the community's knowledge of disasters is not good, as seen from the parameters of knowledge and attitudes towards disaster risk. This is because the community has not participated in socialization and training on community participation in reducing the risk of flooding in the village.